Early intervention for depression and anxiety in 16-18-year-olds: protocol for a feasibility cluster randomised controlled trial of open-access psychological workshops in schools (DISCOVER) - Michelson, D; Sclare, I; Stahl, D; Morant, N; Bonin, E; Brown, J (Elsevier, 2016)
Adolescence is a vulnerable period for the development of mental health problems. The DISCOVER intervention aims to provide accessible, acceptable and cost-effective psychological support for stressed adolescents in inner-city secondary schools. The intervention uses age-appropriate cognitive-behavioural therapy (CBT) methods and materials, delivered in an interactive 1-day workshop with additional telephone support. An open-access entry route allows students to self-refer. This protocol describes a feasibility cluster randomised controlled trial (RCT) comparing DISCOVER with a waitlist control condition. The study will run across 10 clusters (secondary schools) in the inner London Boroughs of Southwark and Lambeth. Participants are students aged over 16 years who are seeking help with anxiety and/or depressive symptoms. Key feasibility parameters relate to the proportion of students willing to participate in the research following publicity events; the proportion of students who complete the intervention; and response rates for outcome measures. Outcome variance estimates and intra-cluster correlations will be obtained for future power calculations. Qualitative methods will be used to explore the acceptability of the intervention and research procedures for students and school staff. The feasibility of an economic evaluation will also be examined. The results will (i) determine the appropriateness of proceeding to a definitive full-scale trial; and (ii) inform the development of an optimised version of the DISCOVER intervention that can be tested within feasible parameters.